Bipolar versus Monopolar Transurethral Resection of Prostate in Treatment of Benign Prostatic Enlargement - Thapa, Niraj; Acharya, Ganesh Bhakta; Poudel, Abhishek; Neupane, Ananda; Mishra, Sushil (Birat Journal of Health Sciences, 2021)
Introduction: Bipolar transurethral resection (B-TURP) is an effective modality for surgery of Benign Prostatic Obstruction, and has been widely studied for its efficacy and safety against the well-established method; Monopolar Transurethral resection (M-TURP). Objectives: The study aimed to assess the feasibility of B-TURP over M-TURP in terms of hospital stay, resection time, resected tissue volume, changes in hemoglobin and sodium, blood transfusion required, complications like TUR syndrome, clot retention and hemorrhagic episodes. Methodology: An analytical study was done in cases who underwent TURP from August 2018 to August 2020. Parameters like hospital stay, resection time, resected tissue volume, changes in hemoglobin and sodium, blood transfusion required, complications like TUR syndrome, clot retention and hemorrhagic episodes were compared in between B-TURP and M-TURP. Statistical analysis was done using SPSS 22.0 software. Results: Seventy-three patients were compared in this study; 33 had undergone B-TURP and 40 patients had undergone M-TURP. Total hospital stay was slightly lesser in B-TURP. The post-operative Hb in M-TURP was significantly lesser than B-TURP (11.10±1.321 vs 12.24±1.225, P<0.001). Although the drop in hemoglobin was statistically significant in both the groups, the hemoglobin drop was slightly lesser in B-TURP. The mean difference in pre and post-operative hemoglobin was 1.148 in M-TURP and 0.181 in B-TURP. TUR syndrome was significantly higher in M-TURP (6,8.2% vs 0, 0%; P=0.029). There was no significant difference in between resection time, post-operative sodium, post-operative hemorrhagic episodes, clot retention and blood transfusions. Conclusion: Bipolar TURP is safe and effective for transurethral resection of prostate with relative shorter hospital stay, lesser bleeding and TUR syndrome in comparison to Monopolar TURP.